'Surrounded with so much uncertainty': asylum seekers and manufactured precarity in Australia. Issue 5 (4th April 2019) - van Kooy, John; Bowman, Dina
ABSTRACT: In Australia, nearly 30, 000 asylum seekers have the legal right to work, but their temporary and conditional migration status exposes them to work-related precarity. This article draws on a small qualitative study that examined asylum seekers' experiences of seeking work and achieving economic security. Over an 18-month period, 29 semi-structured interviews with asylum seekers who had work rights in Australia were conducted. It provides insights into how restrictive immigration policies manufacture precarity through short-term, conditional visas, resulting in employer risk aversion, segmentation into insecure work, and in-work instability and mistreatment. Asylum seekers manage their experiences and feelings of pervasive insecurity through individual coping and survival strategies.